Parents' Experiences as Predictors of State Accountability Measures of Schools' Facilitation of Parent Involvement. (January 2016) - Elbaum, Batya; Blatz, Erin T.; Rodriguez, Raymond J.
The aim of this study was to ascertain which dimensions of parents' experiences with schools are most strongly associated with parents' perceptions that schools are or are not facilitating parent involvement as mandated by the federal accountability system under the Individuals With Disabilities Education Act (IDEA). Participants were 92 parents of students with disabilities from 18 schools in 8 school districts in a large southeastern state. Parents completed the quantitative measure used by their state to report on schools' parent engagement efforts; they then described their experiences collaborating with their child's school. Data from the qualitative analysis of parents' comments were transformed into quantitative variables used to predict success, defined as meeting the state's standard on the quantitative measure of schools' facilitation of parent involvement. Results suggested that schools prioritize responsive communication with parents and careful monitoring of students' progress to improve collaborative relationships with parents of students with disabilities.